Smooth operating and other social acts - Williams, Roland Leander, 1953- (State University of New York Press, 2022)
An engaging homage to African American resilience and resourcefulness in US literature and culture.
Description based upon print version of record.
Keywords: American fiction -- 19th century -- History and criticism.; American fiction -- 20th century -- History and criticism.; African Americans in literature.; Stereotypes (Social psychology) in literature.; Role playing in literature.; Race relations in literature.; Slavery in literature.; Roman américain -- 19e siècle -- Histoire et critique.; Roman américain -- 20e siècle -- Histoire et critique.; Noirs américains dans la littérature.; Stéréotypes dans la littérature.; Jeu de rôle dans la littérature.; Relations raciales dans la littérature.; Esclavage dans la littérature.; African Americans in literature; American fiction; Race relations in literature; Role playing in literature; Slavery in literature; Stereotypes (Social psychology) in literature; 1800-1999; Criticism, interpretation, etc.; Literary criticism.; Critiques littéraires.